Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1253/circj.71.1862
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results of Coronary Revascularization in Left Ventricular Dysfunction

Abstract: DefinitionsThe number of diseased vessels was defined as the number of the 3 major coronary perfusion territories affected. Perioperative insertion of an intra-aortic balloon pump (IABP) was defined as a procedure for improving hemodynamics in the presence of cardiogenic shock. Postoperative cerebrovascular accident (CVA) was defined as a focal or global neurological deficit confirmed by a neurologist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
3
12
1
Order By: Relevance
“…The steep operative mortality in the LEF group (13.5%) was considerably higher compared to the published mortality of non-reoperative (first time) cardiac surgery patients with low LVEF (5.6% to 11%) (13)(14)(15) and to the previously published operative mortality in all re-AVR patients (4.5% to 5.1%) (8,9), to which the 3.2% mortality of our re-AVR HEF group compares favorably. The contrasting outcomes of re-AVR LEF patients to both HEF and historic groups stress the increased risk conferred by the presence of low ventricular contractility and a prior sternotomy.…”
Section: Discussioncontrasting
confidence: 58%
“…The steep operative mortality in the LEF group (13.5%) was considerably higher compared to the published mortality of non-reoperative (first time) cardiac surgery patients with low LVEF (5.6% to 11%) (13)(14)(15) and to the previously published operative mortality in all re-AVR patients (4.5% to 5.1%) (8,9), to which the 3.2% mortality of our re-AVR HEF group compares favorably. The contrasting outcomes of re-AVR LEF patients to both HEF and historic groups stress the increased risk conferred by the presence of low ventricular contractility and a prior sternotomy.…”
Section: Discussioncontrasting
confidence: 58%
“…In a study by Shah and colleagues [20], the 5-year survival rate in patients with an EF of < 35% was 55%, and the 10-year survival rate was 23.9%. In a recent study of patients with an EF of ≤ 30, approximately 80% were alive 5 years after surgery, and 45% were alive 10 years after surgery [24]. A 20-year survival study by Weintraub and colleagues showed that a low EF independently predicted poor long-term survival after CABG, although the subjects experienced good relief from angina [25].…”
Section: Discussionmentioning
confidence: 99%
“…Case selection has been shown to be an important factor in achieving a favorable outcome after CABG in patients with a low EF [24]. Our study included patients without preoperative viability test results and those with a ventricular aneurysm or associated mild or moderate mitral regurgitation.…”
Section: Discussionmentioning
confidence: 99%
“…Within this study group, the early mortality was significantly decreased from 11.8% in the first half of the study period to 6.7% in the second half of the study period. Improvement in early outcome of patients with low EF has been attributed to improved operative techniques and better patient preoperative screening and selection 17 …”
Section: Discussionmentioning
confidence: 99%